The History of Introduction and Present Distribution of Elaeagnus angustifolia L. in the Black Sea Region of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
By the end of the 20th Century active dispersal Elaeagnus angustifolia L. has been observed in the Northern Black Sea region of Ukraine (Odesa, Mykolayiv, Kherson, and Crimea Regions). The initial centers of its invasion were plantations of trees adjacent to roads where this species was widely cultivated; later E. angustifolia spread spontaneously due to its abundant fruit reproduction. By its degree of naturalization it is regarded as an invasive plant (agriophyte) penetrated natural and disturbed plant communities. In man-made habitats, such as roadsides, railway embankments, waste grounds, and pastures, it usually occurs as solitary trees or in small groups of trees. In semi-natural habitats it usually prefers riverbank habitats and sandy steppes, overgrazed pastures, open sandy areas, coastal sand dunes, floodplain meadows, often saline meadow, stony and steppe-covered slopes of ravines, and rocky screes, mostly on dry soils. In this paper we present a distribution map of E. angustifolia in the Black Sea region of Ukraine.
Keywords: Elaeagnus angustifolia distribution, Black Sea region, Ukraine.